2022
DOI: 10.1111/cns.13850
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rph3A in brain injury induced by experimental cerebral ischemia‐reperfusion model in rats

Abstract: Aim The aim was to study the role of Rph3A in neuronal injury induced by cerebral ischemia‐reperfusion. Methods The protein and mRNA levels of Rph3A in penumbra were detected by Western blot. The localization of Rph3A in different cell types in penumbra was detected by immunofluorescence. Apoptosis in the brain was detected by TUNEL staining. We tested neurobehavioral evaluation using rotarod test, adhesive‐removal test, and Morris Water maze test. We examined the expression and localization of Rph3A in cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, a recent study has demonstrated that RPH3A overexpression improves motor behavior in the PD mice model, and is a novel molecular target to counteract α-syn-induced synaptic failure (49). Besides, a study has suggested that the increase in Rph3A in the brain penumbra may be an endogenous protective mechanism against ischemia-reperfusion injury, which is mainly dominated by astrocytes (50). RPH3A loss correlated with dementia severity, cholinergic deafferentation, and increased β-amyloid (Aβ) concentrations (51).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has demonstrated that RPH3A overexpression improves motor behavior in the PD mice model, and is a novel molecular target to counteract α-syn-induced synaptic failure (49). Besides, a study has suggested that the increase in Rph3A in the brain penumbra may be an endogenous protective mechanism against ischemia-reperfusion injury, which is mainly dominated by astrocytes (50). RPH3A loss correlated with dementia severity, cholinergic deafferentation, and increased β-amyloid (Aβ) concentrations (51).…”
Section: Discussionmentioning
confidence: 99%
“…S100a8 and S100a9 upregulation is representative of a pro-inflammatory state in injured peripheral nerves and induces microglia activation [ 17 , 80 ]. Finally, several genes related to neuronal function are downregulated in P1.hMR mice, such as genes encoding for rabphilin 3a ( Rph3a ), secretogranin ( Scg2 ) and Kinesin Family Member 5A ( Kif5a ), respectively, important for synaptic transmission [ 67 , 71 , 87 ], abundantly expressed by trigeminal neurons innervating the eye [ 63 , 64 ] and a crucial regulator of neurodegeneration [ 65 ]. Whilst an important proportion of neuronal RNA is missing due to the lack of neuronal bodies in the rodent choroid, the regulated genes/pathways reflect potential underlying mechanisms linking chorioretinopathy with choroidal neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of RPH3A could aggravate brain injury. Therefore, the increase in RPH3A may be an endogenous protective mechanism against brain injury [ 39 ]. RPH3A was also shown to be a novel target for levodopa-induced dyskinesias [ 40 ].…”
Section: Discussionmentioning
confidence: 99%